دراسة العلاقة بين درجةِ الضمورِ الزغابي و كلٍّ من شدّة التظاهرات السريرية ومستوى ارتفاع قيمة Anti- tissue transglutaminase IgA عند مرضى الداء الزُلاقي البالغين - انطانيوس ميلاد; يازجي هيثم; عوض رفيق (Latakia University Journal -Medical Sciences Series, 2017)
الداء الزلاقي هو مرض مناعي ذاتي تحدث فيه استجابة مناعية غير ملائمة تجاه الغلوتين تؤدي الى تأثيرات هضمية و جهازية مختلفة . للداء الزلاقي 4 أنماط ( الكلاسيكي ، اللانمطي ، الصامت ، الكامن ). ان تشخيص المرض يتم عبر الربط بين القصة المرضية و الفحص السريري مع الاختبارات المصلية ونتائج التنظير العلوي و الخزعات المتعددة من العفج . تم اجراء هذه البحث لدراسة العلاقة بين anti-tTG IgA و شدة التغيرات النسيجية بالخزعة و من أجل دراسة العلاقة بين شدة التظاهرات السريرية و درجة الضمور الزغابي .أجريت دراسة للمرضى البالغين المراجعين لمشفى الأسد و تشرين الجامعيين مابين عامي 2015 و 2016 ، حيث أجري لهم أضداد anti-tTG نمط IgA وعندما كانت النتائج إيجابية أجرينا للمرضى تنظير هضمي علوي مع خزعات عفج و تم تشخيص الداء الزلاقي اعتمادا على إيجابية الأضداد و وجود خزعة عفج Marsh ≥ 2 . النتائج : 79 مريضا كانت لديهم أضداد TTg IgA إيجابية و هؤلاء تم اجراء خزعات عفج لديهم و تم تشخيص الداء الزلاقي لدى 71 مريضا منهم أي بلغت نسبة الداء الزلاقي في مجموعة الدراسة 89.873 % ، وجدنا أنه لا يوجد ارتباط بين رقم الأضداد و الجنس أو العمر ، تنوعت التظاهرات السريرية و كان أكثرها شيوعا فقر دم بعوز الحديد (49.3 %) و ثم الألم البطني (39.4%) ، وجدنا بالدراسة أنه لايوجد علاقة بين قيم anti-tTG IgA و بين شدة التظاهرات السريرية أو القيم المخبرية و بأنه أيضا لا علاقة بين درجة الأذية النسيجية و بين شدة التظاهرات السريرية ، بينما لوحظ ترقي الأذية النسيجية بازدياد قيم anti-tTG IgA . و استطعنا تحديد قيمة ل Anti TTg IgA مشخصة للداء الزلاقي دون الحاجة لخزعات العفج بحساسية 80.3 % و نوعية تعادل 100 % و هذه القيمة هي ( الرقم الأعلى للطبيعي مضروب ب 11.35 ) . و توصلنا الى أن الاعتلال المعوي الخفيف في الداء الزلاقي هو مشكلة جدية تتطلب الالتزام الصارم بحمية خالية الغلوتين منعا من اختلاطات هذا الداء و مضاعفاته . Celiac disease is a condition in which the immune system responds abnormally to a protein called gluten , and leads to many gastrointestinal and systemic effects . There are four categories of celiac disease : (classical, atypical, silent and latent) . The diagnosis of celiac disease is established by a combination of the history , physical examination , serological tests , upper endoscopy results and multiple biopsies of the duodenum . This research is designed to study the correlation between the titres of Anti TTg IgA and between the severity of histological changes in the biopsy , and to study the correlation between the severity of clinical manifestations and between the degree of villous atrophy . The study included the adult patients who presented to Al-Assad University Hospital and Tishreen University Hospital during the period 2015- 2016 . We measured Anti tTG IgA titers . when the results were positive, patients went to upper endoscopy with duodenal biopsies . The diagnosis of celiac disease was made on the base of positive antibodies and the presence of duodenal biopsy of Marsh ≥ 2 . The results : 79 patients had positive IgA Anti tTG , and they had duodenal biopsies , the diagnosis of celiac disease was made in 71 of them . The celiac disease was found in % 89.873 of the study group . We found no correlation between the titers of Anti TTg IgA and between sex or age. The clinical manifestations varied , iron deficiency anemia was the most common (%49.3) and abdominal pain (%39.4) . Also, we found no correlation between the titers of Anti tTG IgA and between the severity of clinical manifestations or laboratory results . There was no correlation between the degree of histological damage and between the severity of clinical manifestations . We noticed that histological injury had progressed whenever the titers of Anti tTG IgA had raised . We were able to determine the titer of Anti tTG IgA in which it was diagnostic for celiac disease without the need for duodenal biopsies with sensitivity of 80.3% and specificity equivalent to 100% and this titer was : (the upper limit of the laboratory’s normal serum value multiplied by 11.35). We have reached that mild enteropathy in celiac disease is a serious problem that requires strict adherence to a free gluten diet in order to prevent from the complications of the disease .